Formation and corrosion resistance of a novel Co–Ti–Mo composite chromium‐free chemical conversion coating on LY12 aluminum alloy. Issue 5 (6th January 2022) - Qian, Xuzheng; Zhao, Waner; Zhan, Wen; Zhang, Tianyue; Pan, Jingjing; Liu, Yiting
Abstract: A novel type of Co–Ti–Mo conversion coating (CoTiMoCC) was prepared on LY12 aluminum alloy, furthermore the optimal formula and the effect of conversion time (CTI) were studied in detail. The micromorphology and phase compositions were systematically investigated by scanning electron microscopy and X‐ray photoelectron spectroscopy, and the corrosion resistance was determined by dropping test, electrochemical tests, and immersion test. Results reveal that the best formula of CoTiMoCC is Co2 SO4 : 2.0 g/L, H2 TiF6 : 1.5 ml/L, and Na2 MoO4 : 1.0 g/L and the corresponding optimal CTI is 16 min. Significantly, the micromorphology of CoTiMoCC under the best conversion condition is relatively smooth, continuous, and dense, and the major elements on the surface are Co, Ti, Mo, Al, O, and F. The phase compositions mainly consist of CoO, Co3 O4, MoO3, Mo2 O5, TiO2, and Al2 O3, as well as a small quantity of AlF3 ·3H2 O and Na3 AlF6 . Compared with the Al alloy matrix, CoTiMoCC acquires an order of magnitude lower I corr and thus significantly reduces its corrosion rate, which is also confirmed by electrochemical impedance spectroscopy results. Further study of immersion test exhibits that the corrosion resistance of CoTiMoCC is approximately five times that of Al alloy matrix, and no obvious corrosion spots are generated on its surface. Abstract : This study presents the corrosion protection properties of CoTiMoCC on LY12 aluminum alloy. The immersion test indicates that CoTiMoCC can avoid the appearance of pitting corrosion within the test time range, and the corrosion resistance of CoTiMoCC was tremendously improved by five times that of the Al alloy matrix.